(untitled) (Experimental biology, 2015)
The research of the heart rate variability in one’s sleep at a height of 5115–7600 м, executed at ascent on Everest, has determined the increase of general power spectrum of the heart rate variability and the heart rate at climb to 7100 м with the following tendency of the general power spectrum to decrease and progressive increase of the heart rate at a height of 7600 m. Evidence of the heart rate’s and general power spectrum’s of the HRV changes depend on altitude and length of stay in conditions of high-mountain area.